Photomorphogenesis and content of carbohydrates in the axial organs of field pean seedlings under the influence of selective light - V. V. Zhmurko; O. O. Avksentieva; Y. D. Batuieva (Біофізичний вісник, 2022)
Background: Light is a multifaceted exogenous factor that plays an important role in plant growth and development. The spectral composition of light is determinative for the regulation of photomorphogenetic processes in plants. Nowadays plants have several groups of photoreceptors that include receptors of red (RL) and far red light (FRL) — phytochromes; receptors of UV-A, blue (BL) and green (GL) light — cryptochromes, phototropins, proteins of the ZEITLUPE family, as well as the UV-B receptor — UVR8 protein. One of the possible mechanisms that realize an activation of photoreceptor systems in the plant may be concerned with carbohydrate metabolism. The research of morphogenetic reactions of seedlings under the action of selective light irradiation by activating photoreceptor systems is important for understanding the mechanisms of regulation of the program of plant organism`s ontogenesis.